Diseño e implementación de un algoritmo para la navegación autónoma de un robot diferencial en el traslado de material entre celdas de trabajo - Rodríguez Hernández, Sandra Alejandra (My University, 2024)
This thesis addresses the design of a path planning algorithm for a differential drive robot whose task is to transport materials between work cells within a known environment. The characteristics of differential drive robots are detailed to understand their operation and apply planning algorithms to them, thus enabling transportation between stations within work cells. Additionally, a thorough investigation of classical path planning algorithms, such as the A* algorithm and the Probabilistic Roadmap, is conducted. A control system is then added to track the path generated by the planning algorithms, and finally, all of this is integrated into the CoppeliaSim simulator. The programming of the path planning algorithm and the control system is done in MATLAB, maintaining the connection with CoppeliaSim for visualization until the completion of the trajectory.
Keywords: Algoritmo de planificación; Robot diferencial; Campus Tijuana